(untitled) (Studia Iberystyczne, 2014)
MARTIAL POLITICS: ADULTERY, FAMILY STRUCTURES AND PATERNITY IN CAMILO CASTELO BRANCO This article discusses a number of texts written by Camilo in the early 1870s in response to the prosecution and conviction of his friend Vieira de Castro for the murder of his adulterous wife, and in the wake of the controversial book by Alexandre Dumas Fils, L’homme‑femme, of 1872, which sought to justify such actions. These texts demonstrate inconsistencies between a very modern, emancipatory stance adopted in the leaflet A Espada de Alexandre and the more patriarchal tone of Camilo’s fictional works written during the same period. This paper seeks to attribute these contradictions to an unresolved preoccupation on Camilo’s part with the authority traditionally assigned to the male in matters of sexuality and marital convention, even though a closer examination of the texts provides ample evidence for regarding these very same attitudes as outdated.